Double bridged μ2-Halide Cu (II) complexes for the electrocatalytic reduction of CO2. (20th October 2019) - Sadehvand, Maryam; Amiri, Ahmad; Tirani, Farzaneh Fadaei; Gu, Jun; Schenk-Joß, Kurt
Abstract: Two dicopper (II) complexes of general formula [CuLX2 ]2 {L = 2, 5-diphenyl-3, 4(2-pyridyl) cyclopenta-2, 4-dien-1-one, X = Cl (1 ) or Br (2 )} have been synthesized and characterized by elemental analysis, IR, UV–Vis spectroscopic methods. The crystal structures of both complexes have been determined by single-crystal X-ray diffraction;1 and2 have binuclear structures and Cu (II) centres in both complexes adopt a distorted square pyramidal geometry. Two [CuLX] (X = Cl or Br) units in both complexes are linked via μ-X coordination bridge modes with the Cu–Cu distances of 3.534 and 3.716 Å for1 and2 respectively. The electrochemical behaviour of the free L ligand and the corresponding Cu (II) complexes was studied in acetonitrile. The cyclic voltammetry of the complexes1 and2 show three ligand based reduction processes and two metal-centred reductions that are assigned to copper (II) to copper (I) and copper (I) to copper (0). The electrocatalytic activity for the reduction of CO2 of the two complexes was investigated; both complexes are active for the CO2 reduction and result in the formation of CO.